1996
DOI: 10.1083/jcb.133.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Integrin alpha subunit ratios, cytoplasmic domains, and growth factor synergy regulate muscle proliferation and differentiation.

Abstract: Abstract. The role of integrins in muscle differentiation was addressed by ectopic expression of integrin o~ subunits in primary quail skeletal muscle, a culture system particularly amenable to efficient transfection and expression of exogenous genes. Ectopic expression of either the human a5 subunit or the chicken et6 subunit produced contrasting phenotypes. The ot5-transfected myoblasts remain in the proliferative phase and are differentiation inhibited even in confluent cultures. In contrast, myoblasts that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 69 publications
9
150
0
5
Order By: Relevance
“…In vitro studies have shown that ␣6␤1 is able to inhibit proliferation and stimulate differentiation of myoblasts (Sastry et al, 1996(Sastry et al, , 1999 and laminin promotes myoblast differentiation in vitro, inducing them to become postmitotic, fusion-capable, and myosin-and desmin-positive (von der Mark and Ocalan, 1989). In fact, it has been demonstrated recently that the ECM is necessary for skeletal muscle differentiation, independently of MRF expression, suggesting that, upon binding to the ECM, integrins generate signals that drive skeletal muscle differentiation (Osses and Brandan, 2002).…”
Section: Laminin Receptor ␣6␤1 In Epaxial Myotome Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that ␣6␤1 is able to inhibit proliferation and stimulate differentiation of myoblasts (Sastry et al, 1996(Sastry et al, , 1999 and laminin promotes myoblast differentiation in vitro, inducing them to become postmitotic, fusion-capable, and myosin-and desmin-positive (von der Mark and Ocalan, 1989). In fact, it has been demonstrated recently that the ECM is necessary for skeletal muscle differentiation, independently of MRF expression, suggesting that, upon binding to the ECM, integrins generate signals that drive skeletal muscle differentiation (Osses and Brandan, 2002).…”
Section: Laminin Receptor ␣6␤1 In Epaxial Myotome Formationmentioning
confidence: 99%
“…Of these, the roles of the fibronectin receptor ␣5␤1 and the laminin receptor ␣7␤1 are the best studied. ␣5␤1 promotes proliferation and inhibits differentiation of myoblasts in vitro (Blaschuk and Holland, 1994;Boettiger et al, 1995;Sastry et al, 1996), whereas ␣7␤1 is thought to promote the maturation and survival of myotubes (Song et al, 1992;Vachon et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that proliferation of cells cultured in 2D on matrix depends not only on support compliance (stiffness being generally associated with proliferation), but also depends on the type of integrin engaged. Thus, a5b1, a1b1 or avb3 trigger cell proliferation through a Shc/Ras/ERK module, whereas a2b1, a3b1, or a6b1 activation results in cell growth inhibition, eventually associated with cell differentiation or even programmed cell death (Kubota et al, 1988;Varner et al, 1995;Sastry et al, 1996;Wary et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Integrins activate signaling pathways that are either common to all integrins or heterodimerspecific (Giancotti, 1997). The cytoplasmic domains of ␣ subunits may trigger signaling events that are specific for each individual integrin heterodimers (Sastry et al, 1996;Zhang et al, 1995). In addition, coupling of integrin receptors to MAPK pathways has been reported (Chen et al, 1994).…”
mentioning
confidence: 99%